Job characteristics: their relationship to job satisfaction, stress and depression - Steyn, Renier (J Psychol Afr, 2014)
This study investigated the influences of job characteristics on job satisfaction, stress and depression among South African white collar workers. Participants were managers in full-time employment with large organisations. They completed the Job Diagnostic Survey, the Perceived Stress Scale and the Beck Depression Inventory. A regression approach was used to predict job satisfaction, stress and depression from job characteristics. Job characteristics (skill variety, task identity, task significance, autonomy and feedback) predicted job satisfaction, as well as stress and depression. Job characteristics are weak predictors of perceived stress and depression. Work related factors, such as interpersonal relations and organisational culture, may better predict mental health in work settings.